ANALISIS VOICE NOTE WHATSAPP SEBAGAI MEDIA UNTUK PENYEBARLUASAN INFORMASI DIKALANGAN REMAJA DESA MOJOSARI KECAMATAN KAUMAN KABUPATEN TULUNGAGUNG - Nasrullah, Ikhsan; Fikriansyah Wicaksono, Mochammad (UPT Perpustakaan Universitas Bengkulu, 2024)
ABSTRACT Social media has become one of the most frequently used platforms for disseminating information. One of the social media platforms often used is WhatsApp. WhatsApp has many users, including children, teenagers, and adults. On WhatsApp, there is a Voice Note feature that facilitates the dissemination of information, particularly among teenagers in Mojosari Village, Kauman District, Tulungagung Regency. The purpose of this research is to understand the role of WhatsApp Voice Notes as a medium for disseminating information, especially among teenagers in Mojosari Village, Kauman District, Tulungagung Regency. This study uses descriptive qualitative research methods. Data were obtained from field interviews and then analyzed by reducing data, presenting data, and drawing conclusions. The results of the study indicate that WhatsApp Voice Notes play a role in the dissemination of information among teenagers. The role is that voice notes make it easy to disseminate information through WhatsApp. The content of Voice Note information is easy to understand, so the information received can reduce misunderstandings. Keywords: Voice Note, Information Sharing, Information Dissemination.